Multilocational validation of integrated management practices for Sclerotinia rot of Indian mustard (Brassica juncea) - YADAV, M S; AHMAD, N; SINGH, S; YADAVA, D K; GODIKA, S; GAUR, R B (The Indian Journal of Agricultural Sciences, 2014)
Field studies were conducted from 2008 to 2011 on integrated management of Sclerotinia rot of Indian mustard (Brassica juncea L. Czerns & Coss.) involving Trichoderma mixture (T. viride + T. hamatum) formulation (2×109 cfu/g) through seed treatment (10 g/kg), soil application (2.5 kg/ha) pre-incubated in farmyard manure and foliar sprays (0.2%) at 50 and 70 days after sowing along with improved cultural practices at Indian Agricultural Research Institute, New Delhi, which reduced the disease incidence up to a minimum of 11.1% and increased the seed yield up to a maximum of 2.72 tonnes/ha as compared to control (disease incidence 26.9% and seed yield 1.77 tonnes/ha). Validation of management practices were also undertaken during 2008 to 2011 in farmer’s participatory mode under three different agro climates, Zone 1b and 3b in Rajasthan and south-west zone in Haryana. The validation studies revealed that integrated management strategies based on Trichoderma resulted in minimum Sclerotinia rot incidence (mean values of three regions 5.6%) and maximum seed yield (2.19 tonnes/ha) as compared to garlic clove extract (mean values 10.3% and seed yield 1.90 tonnes/ ha) and Farmers’ practices (mean values 19.2% and seed yield 1.66 tonnes/ha). Integrated management strategies based on Trichoderma spp. was found economically viable as indicated by incremental cost: benefit ratio ranging from 1:3.1 to 1:3.8 that was different with garlic clove extract (1:1.2 to 1:2.0), besides mustard seed was produced without any application of toxic fungicides.